Chronic lymphocytic leukemia: novel prognostic factors and their relevance for risk-adapted therapeutic strategies - M Montillo; T Hamblin; M Hallek; E Montserrat; E Morra (Haematologica, 2005)
BACKGROUND AND OBJECTIVES: Many years ago it was established that prompt treatment of early stage chronic lymphocytic leukemia (CLL), the stage at which almost two-thirds of CLL patients present, has no benefit over a management of watching and waiting, then treating progression. However, this fact was based on series treated ineffectually with chlorambucil, which were not stratified according to prognostic markers. DESIGN AND METHODS: The prognosis and clinical course of CLL are heterogeneous. While some patients may have a normal life expectancy without requiring treatment, others die of drug-resistant disease as early as within two years of presentation. However, unlike the situation in non-Hodgkin’s lymphoma, there is no standard Prognostic Index that can be used to group patients with CLL according to likely outcome or to guide treatment. RESULTS: A number of clinical and biological factors of prognostic relevance, which may add to the classical assessment provided by the staging systems, have been identified. These include clinical characteristics, such as age, gender and performance status, and laboratory parameters reflecting the tumor burden or disease activity, such as lymphocyte count, lactate dehydrogenase (LDH) increase, bone marrow infiltration pattern or lymphocyte doubling time. Recently more informative prognostic parameters have been identified: serum markers such as soluble CD23, b2-microglobulin or thymidine kinase and genetic markers of tumor cells, such as genomic aberrations, gene abnormalities (p53, ATM), the mutation status of the variable segments of the immunoglobulin heavy chain genes (IGVH) or surrogate markers for these factors, such as CD38 and ZAP-70. INTERPRETATION AND CONCLUSIONS: From the clinician’s perspective the importance of this new knowledge is how it affects treatment. It is now possible to produce molecular remissions even in advanced disease using combinations of purine analogs and monoclonal antibodies. Moreover, potentially curative therapeutic modalities such as autologous and allogeneic stem cell transplantation are becoming safer. Clinical trials of effective treatment stratified by more reliable prognostic markers are surely now warranted.